Heterogeneous distribution of exocytotic microdomains in adrenal chromaffin cells resolved by high‐density diamond ultra‐microelectrode arrays. (27th June 2014) - Gosso, Sara; Turturici, Marco; Franchino, Claudio; Colombo, Elisabetta; Pasquarelli, Alberto; Carbone, Emilio; Carabelli, Valentina
Abstract : Key points: A planar nanocrystalline diamond array with nine ultra‐microelectrodes (9‐Ch NCD‐UMEA) has been designed for high spatial resolution of amperometric recordings in single chromaffin cells. The 9‐Ch NCD‐UMEA operates in voltammetric and amperometric mode to reveal low doses of adrenaline, dopamine and serotonin. The lowest detectable concentration of adrenaline is ∼5 μm . Using mouse and bovine chromaffin cells, single quantal exocytotic events are recorded from nine microareas of 12–27 μm 2 . We found an excellent correspondence with recordings from the cell apex using carbon fibre electrodes. In the bovine, secretion is heterogeneous. There are areas of high and medium activity covering 54% of the cell surface and areas of low and no activity covering the remainder. The 'non‐active zones' (silent) cover 24% of the cell surface and persist for minutes as the 'active zones'. The 9‐Ch NCD‐UMEA brings new insights into the spatial mapping of secretory sites in chromaffin cells. Abstract: Here we describe the ability of a high‐density diamond microelectrode array targeted to resolve multi‐site detection of fast exocytotic events from single cells. The array consists of nine boron‐doped nanocrystalline diamond ultra‐microelectrodes (9‐Ch NCD‐UMEA) radially distributed within a circular area of the dimensions of a single cell. The device can be operated in voltammetric or chronoamperometric configuration. Sensitivity to catecholamines, tested by dose–response calibrations, set the lowest detectable concentration of adrenaline to ∼5 μm . Catecholamine release from bovine or mouse chromaffin cells could be triggered by electrical stimulation or external KCl‐enriched solutions. Spikes detected from the cell apex using carbon fibre microelectrodes showed an excellent correspondence with events measured at the bottom of the cell by the 9‐Ch NCD‐UMEA, confirming the ability of the array to resolve single quantal secretory events. Subcellular localization of exocytosis was provided by assigning each quantal event to one of the nine channels based on its location. The resulting mapping highlights the heterogeneous distribution of secretory activity in cell microdomains of 12–27 μm 2 . In bovine chromaffin cells, secretion was highly heterogeneous with zones of high and medium activity in 54% of the cell surface and zones of low or no activity in the remainder. The 'non‐active' ('silent') zones covered 24% of the total and persisted for 6–8 min, indicating stable location. The 9‐Ch NCD‐UMEA therefore appears suitable for investigating the microdomain organization of neurosecretion with high spatial resolution.